A study on role of LATCH scoring in duration of exclusive breastfeeding in a rural tertiary care hospital, Puducherry: a prospective study - S., Karthika; M., Mathivanan; K., Maheswari; B., Hiremath P.; Devi, M. Jesintha (International Journal of Contemporary Pediatrics, 2019)
Background: Exclusive Breastfeeding (EBF) for 6 months is the optimal way of feeding infants. NFHS4 data shows 45.5% of children were exclusively breastfed at 6 months in Puducherry. The Global Nutrition Targets 2025 aims at increasing EBF rates in first 6 months up to at least 50%. The main objective is to find areas of needed intervention using LATCH scoring and to find factors responsible for fall in rates of EBF. Methods: A prospective study was conducted between November 2017 and April 2019 (1½years). Mothers were educated about breastfeeding. LATCH score assessed at 8 and 48 hours of life. At 48hours, score >8 indicates there is a high chance for EBF for next 6 months and score <8 indicates, mother is having difficulty in feeding and are intervened at this point. Data about EBF and reason for early weaning at 6 weeks and 6 months collected. Results: LATCH score at 8 hours was >8 in infants delivered via NVD: 50% as against 9.6% in babies delivered via LSCS. At 48 hours LATCH score improved in both groups: 60.8% in babies delivered via NVD, 38.3% in babies delivered via LSCS. Compared to Primi-mothers, infants born to multigravida mothers had higher scores at 48 hours: 62.2% as against 31.1%. 84% were EBF at 6 weeks. 51% were EBF at 6 months. When mothers with LATCH score <8 at 48 hours were intervened, EBF rate at 6 weeks improved. Most common reason for early weaning at 6 weeks was maternal problems: 6.6% and at 6 months- due to influence of relatives: 27%. Conclusions: LATCH score helps in predicting breastfeeding duration as early as 48 hours of life. Low scores indicate, it requires intervention and identifies the areas of needed intervention. Counselling regarding EBF must include not only mothers but also relatives.